Premessa / Vorwort (Studia theodisca, 2025)
The fourth volume of “Studia Hölderliniana”, edited by Marco Castellari and Elena Polledri with the collaboration of Stefano Apostolo, is, as usual, published as a special issue of the international journal “Studia theodisca”. It brings together articles and reviews in both German and Italian on the works and reception of the great German poet Friedrich Hölderlin. This issue, in particular, documents the international conference “Wir sind nichts; was wir suchen, ist alles.” Hölderlin zum 250. Geburtstag, which took place during the Hölderlin Year 2020 at Ca’ Foscari University of Venice. In addition to papers derived from this academic event, further studies addressing key issues in international research are included. The closing section features three reviews of significant recent contributions to the philological, critical, and cultural discourse surrounding Hölderlin.In addition to the aforementioned Apostolo, Castellari, and Polledri, contributors to the issue include Bettina Faber, Marco Fiorletta, Sarah Gaber, Ulrich Gaier, Daniele Goldoni, Martin Huber, Francesco Rossi, Franco Toscani, and Giuseppe Vacca. The volume is dedicated to Luigi Reitani (1959-2021), a great scholar and translator whose scholarly legacy still leads us with a competent and sensitive hand through the ‘fragments of the future” of Hölderlin’s poetry.